EKSPRESI âDIRIâ DALAM BAHASA JEPANG - Saifudin, Akhmad (LITE, 2007)
Although Japanese society is known as a collective society, basically, Japanese self-existence is not merging with itscommunity as it is. Japanese characteristics that are oriented to the community â as they are reflected in their vertical society concept and how people differentiate the concept of uchi / soto â do not eliminate Japanese self-existence nor their individualistic. This writing describes about Japanese self-existence in their language by considering the following factors: predicates psychological, addressing and kinship, honorofic and polite expresion, donatory verb, the pronoun jibun, and private/public expression. It can be said that, in order to describe about Japanese self-existence, it is important to identify their absolute/relational self and public/private expression.Keywords: Japanese self-existence, uchi/soto, absolute/relationalself, psychological predicates, Pronoun Jibun